A short remark on Ren–Hu's modification of He's frequency–amplitude formulation and the temperature oscillation in a polar bear hair. Issue 3 (December 2019) - Wang, Qingli; Shi, Xiangyang; Li, Zhengbiao
Recently Zhong-Fu Ren and Gui-Fang Hu suggested a modification of He's frequency–amplitude formulation for nonlinear oscillators. This paper shows that this modification results in a lower accuracy than that by the original one. The temperature oscillation in a polar bear hair is used as an example to illustrate the effectiveness of He's frequency–amplitude formulation.